The Impact of Financial Development on Economic Growth Around the World - Abu-Jamie, Naseem (Journal of Reviews on Global Economics, 2020)
Motivation: This paper aims to examine the impact of financial development on economic growth. Novelty: The study enriching literatures and provide a baseline for further researches. Methodology and Methods: This article uses the system GMM to analyze data, to ride of the reverse causality problem and considering a dynamic model. Data and Empirical Analysis: The used data for 193 countries around the world, the study used domestic credit to the private sector as a percentage of GDP, board money definition M3, and financial market capitalization as proxies to indicate financial development. Whereas GDP per capita growth rate is used as a proxy for economic growth. Policy Considerations: The study finds that there is a significant mild positive impact of financial development on economic growth, this paper recommended further researches to investigate the impact over the developing and developed countries separately by using dynamic models.